Eksplorasi Etnomatematika pada Industri Gerabah di Desa Rendeng, Kecamatan Malo, Kabupaten Bojonegoro - Salsabiila, Fachru Annisa; Setianingsih, Rini (Universitas Negeri Surabaya, 2025)
Culture and mathematics have a close relationship and cannot be separated. One way to connect mathematics learning with everyday life is through the concept of ethnomathematics. Ethnomathematics is an important concept for understanding the role of mathematics in everyday life. By using an ethnomathematics approach, mathematics learning can be delivered contextually according to students' daily lives. Cultural involvement in understanding mathematics through ethnomathematics allows learning to be more relevant and meaningful for students. Therefore, this research was conducted to identify ethnomathematics and ethnomodelling activities found in pottery burning activities in Rendeng Village, Malo District, Bojonegoro Regency. This research is qualitative research with an ethnographic approach. The instruments used in this research were interview guidelines and observation sheets. The subjects in this research were pottery craftsmen in Rendeng Village. Next, the data will be analyzed by condensing data, presenting data, and drawing conclusions. The results of the research show that there are ethnomathematics activities in the pottery firing process, namely counting activities, location determining activities, measuring activities, designing activities, playing activities and explaining activities. There is also ethnomodeling in how to calculate combinations of pottery that can be fired simultaneously to achieve optimal results. The results of this approach are calculations using the simplex method which can be used by teachers as learning material in schools as well as calculations using Excel Solver which can be used by pottery craftsmen in Rendeng Village as a reference for determining the right combination of pottery to achieve optimal results in the pottery firing process. . Thus, the pottery burning activity in Rendeng Village can be a bridge for teachers to teach mathematical concepts at school. The hope is that through this activity, students can more easily understand the mathematical concepts taught in class.